Carolus van Europa. Keizer Karel V in 2000 herdacht - Mout, M.E.H.N. (BMGN - Low Countries Historical Review, 2001)
Th. Coppens, Antonius Mor. Hofschilder van Karel V R. de Dijn, De vrouwen van de keizer. Een tocht door Europa met Karel V A. Kohler, Karl V. 1500-1558. Eine Biographie H. Verbrugge, Keizer Karel. Testament van een Habsburger H. Lox, Van stropdragers en de pot van Olen. Verhalen over Keizer Karel E. Schreurs, De schatkamer van Alamire. Muziek en miniaturen uit keizer Karels tijd (1500-1535) E. Schulin, Kaiser Karl V. Geschichte eines übergroßen Wirkungsbereiches M.F. Alvarez, Carlos V, el césar y el hombre P.N. Palacio, Carolus V imperator F. Maes, The empire resounds. Music in the days of Charles V H. Soly, J. van de Wiele, Carolus. Keizer Karel V 1500-1558 R. Hoozee, J. Tollebeek, T. Verschaffel, Mise-en-scène. Keizer Karel en de verbeelding van de negentiende eeuw H. Soly, Karel V, 1500-1558. De keizer en zijn tijd S. MacDonald, Charles V. Ruler, dynast and defender of the faith 1500-58 W. Blockmans, Keizer Karel V 1500-1558. De utopie van het keizerschap G. Vanpaemel, T. Padmos, Wereldwijs. Wetenschappers rond keizer Karel T. Padmos, G. Vanpaemel, De geleerde wereld van keizer Karel. Catalogus tentoonstelling Wereldwijs. Wetenschappers rond keizer Karel W. Blockmans, Het keizerschap van Karel V. Europese droom versus regionale werklijkheidCarolus of Europe. The Emperor Charles V commemorated in the year 2000The commemoration of 1500, the year of Charles's birth, has led to many and multifarious publications. In some of them a not unattractive mixture of scholarly research and literary imagination prevails. The big exhibitions evoke an image of the Emperor placed on the intersection between political power and cultural flourishing. Specialized studies examine themes from musicology and the history of science. Biographies vary between modest introductions and bulky volumes full of detail. A few research desiderata, especially in the field of economic and financial history, are still unfulfilled. In every book reviewed the European perspective prevails, contrary to the predominantly national approach of bygone days.